Comparative Analysis of Video-Assisted Thoracoscopic Surgery and Open Thoracotomy for Early-Stage Non-Small Cell Lung Cancer: Review - Ibrahim, Osamah Obaid (American Journal of Biomedicine and Pharmacy, 2025)
Video-assisted thoracoscopic surgery (VATS) has increasingly become the modality of choice in the management of patients with early-stage non‑small cell lung cancer (NSCLC). Morbidity and hospitalisation are always lower and shorter in persons undergoing VATS when compared to persons undergoing conventional thoracotomy in systematic reviews. However, it is essential to note that few randomized controlled trials specifically assessing long-term oncologic outcomes exist. The current review is therefore aimed at evaluating and summarizing the literature published over the last decade, with a focus on cancer-free survival, overall survival, postoperative complications, and health-related quality of life. It is limited to situations where lobectomy or segmentectomy was done with a curative intent that was final and where there was a need to compare the VATS technique and open thoracotomy in the environment of early-stage NSCLC. In addition, new surgical methods and the multifactorial determinants influencing the cost-effectiveness of every operative approach will be discussed.